THE ASPECT OF TEACHING THE ITALIAN LANGUAGE IN THE ALBANIAN EDUCATION SYSTEM - Gjoleka, Meri (European Scientific Journal, ESJ, 2015)
The beginning of the 90-s marks a watershed for the Albanian education system in the field of teaching of foreign languages such as: English, French, Italian, German, etc. The opening of Albania to other countries and the new needs for communication brought to the attention of Albanian specialists teaching foreign language, the immediate need to the renewal of the previous curriculum in the field of foreign languages in compliance with the new European models suggested by the Council of Europe. In this context, the teaching of the Italian language, as part of the European linguistic richness, took a special development by highlighting the achievements to date and the prospects for the future. It is through our article that we will try to give an overview of the development of teaching of the Italian language in Albania in all its levels, focusing in particular, on those levels where the interest of the Albanian students and their achievements have been most visible.